Public Goals and Government Expenditures: Are the Solutions of the “Modern Monetary Theory” Realistic? - I. M. Stepnov; Ju. A. Kovalchuk; M. V. Мelnik; T. Petrovic (Финансы: теория и практика)
The relevance is determined by the presence of discussions among economists and political scientists about the state regulation role, especially during crises when governments are expected to provide an economic miracle solution or new measures that are not thought about during periods of growth. The subject of the study is government expenditures, which should be fairly distributed by governments in crisis times with a clear vision and understanding of public goals, for the achievement of which it is necessary to undertake economic changes. Therefore, the purpose of the study is to generalize the results of the discussion about the possibility of changing the economic “mainstream” to the “modern monetary theory” (MMT) and its prospects in public finance management. The research methods include systematic, critical, comparative and cross-country analysis and verification of the realism of the MMT’s proposals. The results of the study made it possible to analyze the economic solutions of the new theory based on the political subtext of the theory itself: is it possible to entrust governments with an unlimited budget filled with the issue of national currency; has there been a need to update public goals; what are the prospects for full employment with government funding of jobs; is it possible for society to subject taxes to increase or is there enough transparency and collection; is inflation dangerous in the current situation and in the future; is the MMT really an economic recipe for politicians focused on achieving public goals, including ecology and inequality. It is concluded that all-round criticism and all-round approval are equally unacceptable in relation to the new theory from the standpoint of practical state regulation. Some elements of the MMT have already been implemented in various countries, both successfully and with negative consequences. Therefore, when considering the MMT in unity with public goals, the criterion of choice should not be the quality of economic decisions, not their elegance and validity, but enforceability in accordance with urgent and strategic tasks that need to be solved by politicians.